PENGARUH BOOK TAX DIFFERENCES TERHADAP PERTUMBUHAN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Delvina Risnanda; Farida Khairani Lubis; Abdul Rasyid (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
This research is conducted to find out the effect of temporary difference on profit growth in manufacturing companies, to find out the effect of permanent difference on profit growth in manufacturing companies, to find out the effect of book tax differences on profit growth in manufacturing companies, and to find out the effect of temporary difference, permanent difference and book tax differences on profit growth in manufacturing companies. The method used in this study is the documentation method. Documentation is the collection of data carried out with the category and classification of materials that are written and related to research problems. Data related to this study include, financial statements in the form of balance sheets and income statements from 2017-2019. And also the study of libraries used by reading books that. This study concludes that temporary difference has a positive and significant effect on profit growth in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Permanent Difference negatively and significantly affects profit growth in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Book Tax Differences has a positive and significant effect on profit growth in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Temporary difference, permanent difference and book tax differences simultaneously positively and significantly affect profit growth in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019.